Star Trek and Utopian future: race, gender and the cultural imagination analysis - Ika Destina Puspita; Widyarini Susilo Putri (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2018)
Science Fiction as one of the popular culture genre, usually take theme about the future and utopias world. One of the popular sci-fi movies serial are Star Trek. The movies have so many issue talks about American dream, the dream of American’s utopia world as the better world for human being. The image of future society represented quit detail and well in these movies. How Star Trek give new perspective of future technology and how the American society in the future depicted in the movies will be discussed using American study theory and semiotic approach. The success of the movies brings the viewers to new world of Star Trek utopia. The world where human lived in peace and prosperity supported with high advance technology.  DOI: 10.26905/enjourme.v2i2.2747